THE IMPACT OF PEER RESPONSE ON EFL LEARNERS’ WRITING DESCRIPTIVE TEXT - Nur Rohmat; Irma Savitri Sadikin (University of Kuningan, 2019)
The aim of this study is to find out whether or not there is a significant difference between students who are taught by using peer response technique and those who are not taught by using peer response technique in writing descriptive text. This study used quantitative research method with quasi-experimental design. The population of this research was the 175 students of tenth grade at SMK Bandung Barat, while the sample was 26 students of X 2 Farmasi and X TLM. Writing test was used as the instrument of the study. The data were collected from the result of pretest and posttest. Then, the gain of both classes was analyzed by using t-test in SPSS. The result of the study showed that the mean of gain score in experimental class was 0.38 and the mean of gain score of students in control class was 0.22. It meant that there was difference in improvement between both classes. The hypotheses testing showed that sig. 2 tailed values (p) was 0.000 while alpha was 0.05. In other words, p . It indicated that H0 was rejected. Therefore, it can be concluded that there is a significant difference between students who are taught by using peer response technique and those who are not taught by using peer response technique in writing descriptive text.Keywords: descriptive text; peer response technique; teaching; writing.